2022
DOI: 10.1097/md.0000000000031716
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rate of hospitalization for severe peptic ulcer in digestive disease emergencies after the pandemic

Abstract: Since December 2019, the novel coronavirus has spread worldwide, affecting more than 510 million people, with more than 6 million deaths. However, some of the potential effects of the pandemic have not been thoroughly studied. We collected data from 2 regional emergency centers from May to November for the years 2015 to 2019, before the pandemic, and from May to November 2020, after the pandemic. We evaluated the incidence of each major type of digestive disease before and after the pandemic in adults at the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The positive correlation between COVID-19 and the incidence of peptic ulcers was suggested by the study of Dao et al, which showed that the incidence of peptic ulcers was significantly higher during the COVID-19 pandemic in 2020 compared to 2019 in the same health facility in Vietnam [ 4 ], and by the study of Jian et al, which confirmed the same findings in two hospitals in Wuhan, China, during the pandemic [ 5 ].…”
Section: Discussionmentioning
confidence: 74%
“…The positive correlation between COVID-19 and the incidence of peptic ulcers was suggested by the study of Dao et al, which showed that the incidence of peptic ulcers was significantly higher during the COVID-19 pandemic in 2020 compared to 2019 in the same health facility in Vietnam [ 4 ], and by the study of Jian et al, which confirmed the same findings in two hospitals in Wuhan, China, during the pandemic [ 5 ].…”
Section: Discussionmentioning
confidence: 74%
“…In line with Dao et al’s study, Jian et al observed that the rate of peptic ulcer disease increased dramatically in two hospitals in Wuhan, China, in 2020. They also observed an increase in the incidence of severe peptic ulcer disease after the pandemic in comparison to the same period before the pandemic [ 76 ]. The negative impact of COVID-19 on peptic ulcer disease should be focused on in the future as well.…”
Section: Discussionmentioning
confidence: 99%